Strategi Bisnis dalam Praktik Manajemen Laba pada Perusahaan Manufaktur di Indonesia - Widyasari, Permata Ayu; Harindahyani, Senny; Rudiawarni, Felizia Arni (University of Merdeka Malang, 2017)
This study investigated whether a firm’s business strategy is associated with real and accrual earnings management. It applied by Miles Snow (1978) business strategy typology and classified business strategy into two dominant and contrast strategy, prospector and defender. Business strategy is how the company make the decision to compete with its competitors and to sell its products. Compare with prospectors, Defenders have the motivation to engage in earnings management with the purpose of maintaining its reputation as a stable company and fulfill the investor’s expectation. Furthermore, this study also examined whether audit quality can decrease real and accrual earnings management. The sample was used in this study are manufacturing firms that are listed in the Indonesia Stock Exchange in period 2011–2014. Hypotheses were tested using multiple linear regressions. Our findings show that the defender has higher absolute real earnings management compare to the prospector, especially for-profit firms. However, absolute real earnings management can be decreased along with the increase in audit quality. Such findings could be a consideration for the investors. On the other hand, the business strategy does not associate with accrual earnings management.DOI: https://doi.org/10.26905/jkdp.v21i3.1179